HEART RATE MEASUREMENT MONITORING USING PULSE HEART RATE SENSOR AND NODEMCU - Muhammad Syahputra Novelan (INFOKUM, 2021)
Health for life is very important to be maintained. everyone needs to pay attention to the health of their bodies, the most important thing is heart health. One of the most important organs for humans is the heart which functions to pump blood throughout the body, as a means of passage in the body and blood works to transport oxygen and nutrients needed by the body's organs. Heart rate beats per minute (bpm) symbolizes the scale to see the state of the heart, and to understand the state of the heart by looking at the size of the heart rate. For this reason, it should be necessary to design a device to detect heart rate, see the normal or abnormal heart rate in every human being and a device designed to be used by every human being without exception. Listen to the development of technology today, many components on the market can be accessed, the NodeMCU microcontroller development board facility as a control center that is connected to a Pulse Heart Rate Sensor, the analog heart rate media reader is then converted into digital data that is read, then communicated using Wifi is integrated with the NodeMCU module so that it can be displayed on a notebook or on an Android smartphone which can be used repeatedly according to measurement needs.